Harnessing Lean and FMEA techniques to eliminate waste and enhance performance in poultry processing - Rofiatul Husna; Rita Ambarwati; Dametken Medihanovna Turekulova (Jurnal Sistem dan Manajemen Industri, 2025)
This study integrates lean manufacturing and failure mode and effects analysis (FMEA) to identify and mitigate production waste and risk in a poultry processing facility. The study identifies dominant waste types, waiting, motion, and over-processing by applying value stream mapping (VSM), fishbone diagram, and FMEA. The highest risk priority number (RPN) of 210 was found in the chilling process, indicating a critical need for corrective action. Implementing proposed improvements such as layout redesign and chiller capacity expansion resulted in measurable gains: a 5.8% reduction in labor costs, a 2.3% drop in operational expenses, and a 1.2% decrease in raw material waste. Compared to prior studies that applied Lean or FMEA separately, this research offers a structured Lean–FMEA framework tailored for the poultry industry. This model enhances efficiency while ensuring food safety and serves as a replicable method for similar industries.